2017
DOI: 10.1002/2016ja023167
|View full text |Cite
|
Sign up to set email alerts
|

Structure, dynamics, and seasonal variability of the Mars‐solar wind interaction: MAVEN Solar Wind Ion Analyzer in‐flight performance and science results

Abstract: We report on the in‐flight performance of the Solar Wind Ion Analyzer (SWIA) and observations of the Mars‐solar wind interaction made during the Mars Atmosphere and Volatile EvolutioN (MAVEN) prime mission and a portion of its extended mission, covering 0.85 Martian years. We describe the data products returned by SWIA and discuss the proper handling of measurements made with different mechanical attenuator states and telemetry modes, and the effects of penetrating and scattered backgrounds, limited phase spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
352
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 232 publications
(374 citation statements)
references
References 135 publications
(211 reference statements)
21
352
1
Order By: Relevance
“…5.2.1 and 5.2.3). Recently Halekas et al (2017) have shown using MAVEN data that SLAMS can occur upstream of the Martian bow shock for near-radial interplanetary magnetic fields, reconfiguring the Martian bow shock. Similarly, Collinson et al (2012) have observed SLAMS upstream of the bow shock of Venus.…”
Section: Discussion and Conclusion On Planetary Bow Shocksmentioning
confidence: 99%
“…5.2.1 and 5.2.3). Recently Halekas et al (2017) have shown using MAVEN data that SLAMS can occur upstream of the Martian bow shock for near-radial interplanetary magnetic fields, reconfiguring the Martian bow shock. Similarly, Collinson et al (2012) have observed SLAMS upstream of the bow shock of Venus.…”
Section: Discussion and Conclusion On Planetary Bow Shocksmentioning
confidence: 99%
“…The upstream solar wind parameters (density, dynamic pressure, and velocity) and IMF are computed from the SWIA onboard moments and MAG measurements (intensity and direction of the magnetic field) following the method by Halekas et al (2016). The SEP fluxes are obtained from the SEP instrument.…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
“…Periods of pristine solar wind were selected by implementing the algorithm developed by Halekas et al (2017), based on measurements of bulk flow speed, proton scalar temperature, spacecraft altitude, and normalized magnetic field fluctuation levels. Periods of pristine solar wind were selected by implementing the algorithm developed by Halekas et al (2017), based on measurements of bulk flow speed, proton scalar temperature, spacecraft altitude, and normalized magnetic field fluctuation levels.…”
Section: Maven Overviewmentioning
confidence: 99%
“…For selection, we require that (1) MAVEN observed both the upstream solar wind and the magnetotail (X MSO ≤ À1 R M ) over the course of a single orbit and (2) upstream parameters met the criteria of the Halekas et al (2017) algorithm. For selection, we require that (1) MAVEN observed both the upstream solar wind and the magnetotail (X MSO ≤ À1 R M ) over the course of a single orbit and (2) upstream parameters met the criteria of the Halekas et al (2017) algorithm.…”
Section: Statisticsmentioning
confidence: 99%